Afiksasi dan Pengaruhnya terhadap Konstruksi Sintaksis Bahasa Jawa Kuna - Muhammad Badrul Anwar; Harum Munazharoh (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
This article departs from the use of language affixation to change syntactic constructions in sentence grammar. Prefixes in Old Javanese are "a-" and "ma-", infixes are "-um-" and "-in-", suffixes are "-i"; “-an”, and “-en”, and the confixes are “ka-an” and “pa-an”. The prefix "a-", "ma-" and the infix "-um-" indicates active voice. While the prefix "ka-", "pa-", and the infix "-in-" indicate passive sentences. Meanwhile, the suffixes "-a", "-en", and "-aken" can be active and passive sentences, depending on the grammatical meaning and other supporting affixes. The method in this research is qualitative. This study found (1) in Old Javanese, active or passive sentences will affect the position of the subject and predicate function in the sentence, (2) the addition of confixes makes the function and syntactic categories in the form of nouns, (3) the role of active sentence verbs refers more to action, while in the passive sentence in the form of events. This research is expected to be able to provide benefits in the form of adding to the repertoire of knowledge in the field of Old Javanese language syntax and can be used as a reference and consideration in further research. Keywords: Affixation, Old Javanese, Syntactic Construction.